EFFECT OF GLYCEROL SEPARATION ON PALM OIL TRANSESTERIFICATION - Budy Rahmat; Imas Siti Setiasih; Roni Kastaman (Universitas Gadjah Mada, 2012)
This research was aimed to study the effect of glycerol separation on palm oil transesterification. Objectives of this study were to suppress the use of excess methanol and shorten the processing time. This research consisted of: design-build reactor, the effect of the glycerol separation on the transesterification reaction, characterization of biodiesel, and mass balance analysis. The reactor was designed by integrating circulate stirrer pump, static mixer, and sprayer that will bring out the intense reaction in the outer tank reactor. The experiment in this research was the treatment of decreasing the quantity of methanol to 5:1 molar ratio and reducing of processing time to 20 min, which was arranged in a completely randomized factorial design. The result showed that, (i) the stirring system was effectively worked outside the reactor tank, and in its reactor tank occurred glycerol separation during the process; (ii) the rate of glycerol during the process followed the inverse regression equation of Ŷ = 66.44-351.17 X-1; (iii) the decrease in the level of methanol to 5:1 molar ratio and the reduction of processing time to 20 min in this engineering did not influence the biodiesel yield and quality that met the SNI 04-7182-2006 standard.